(untitled) (Academic Journal of International University of Erbil, 2025)
This paper examines how legal frameworks and institutional structures influence accounting practices and financial transparency within the Iraqi banking industry from 2010 to 2024. Based on a balanced panel dataset of 47 banks derived using official data, which comprise the Central Bank of Iraq, and published annual bank data, the study determines some main determinants of transparency. The use of International Financial Reporting Standards (IFRS), strict exercise of anti-corruption, efficacy of audit, and judicial regimes of administration have been identified to drastically improve financial disclosure. The impact of the clarity of the tax law is less extensive, although statistically significant. However, contrary to this, the size of a company does not have a great influence on transparency; thus, the quality of governance is more influential than the size of the organization. In an endeavor to deal with the possible endogeneity of the research and variation over time in the panel data, the research uses the Generalized Method of Moments (GMM) estimation procedure. The approach is more suitable with the lagged financial panel data, as it is used in providing unbiased and efficient estimates. Diagnostic tests indicate robustness in the model, such as the Hansen J-statistic and no second-order autocorrelation. The results have viable suggestions for policymakers and banking regulators in Iraq. The response to this is increasing the enforcement of the law, enforcing compliance with international standards, and enhancing institutional oversight, and as a result, all this has been able to strengthen the credibility and reliability of the financial report. These experiences and lessons are especially useful to new and post-conflict economies interested in modernization of their financial systems and in foreign investment.